The role of affective temperaments and chronotype in pharmacotherapy response in patients with obsessive-compulsive disorder - SAKALLI KANİ, AYŞE; KÖSE, SAMET (TAYLOR & FRANCIS LTD, 2018)
BACKGROUND: Comorbid mood disorders affect the prognosis of obsessive-compulsive disorder (OCD) negatively. Affective temperaments are assumed to be subsyndromal symptoms and precursors of mood disorders, but its effects on OCD outcome still remain unclear. There is a body of evidence, which supports the association between circadian rhythm disturbances and mood disorders in the literature. In contrast, there is limited data concerning the effects of chronobiological differences among the patients with OCD and OCD comorbid mood disorders. The main objective of this present study was to examine the clinical effects of affective temperaments and chronotype differences in patients with OCD. METHODS: The study participants were 76 patients with OCD, who have been under treatment at least for 12 weeks, and 55 healthy controls. The participants were administered the Yale-Brown Obsessive Compulsive Scale, Temperament Evaluation of Memphis, Pisa, Paris, and San Diego Auto-questionnaire, Morningness and Eveningness Questionnaire, Hamilton Depression Rating Scale, and Hamilton Anxiety Scale. RESULTS: OCD patients scored higher in depressive, cyclothymic, irritable, and anxious temperament scores compared to the healthy controls. There were significant differences between patients with remission and not remission in depressive, cyclothymic, irritable, and anxious temperaments. Eveningness chronotype was more frequent in OCD patients; however, the difference was not statistically significant. CONCLUSIONS: Understanding the effects of affective temperaments and chronotype differences on the outcome of patients with OCD might provide valuable insights in developing new treatment approaches especially in treatment-resistant OCD cases.
Keywords: Obsessive-compulsive disorder; affective temperament; chronotype; treatment outcome; circadian rhythm disturbances; comorbidity; BIPOLAR AFFECTIVE-DISORDERS; DELAYED SLEEP PHASE; CLINICAL IMPACT; CIRCADIAN PREFERENCE; MOOD DISORDER; TEMPS-A; OCD; DEPRESSION; COMORBIDITY; FEATURES